2010
DOI: 10.2165/11318000-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In Vivo P-Glycoprotein Phenotyping Probes

Abstract: Drug transporters are involved in clinically relevant drug-drug interactions. P-glycoprotein (P-gp) is an efflux transporter that displays genetic polymorphism. Phenotyping permits evaluation of real-time, in vivo P-gp activity and P-gp-mediated drug-drug interactions. Digoxin, fexofenadine, talinolol and quinidine are commonly used probe drugs for P-gp phenotyping. Although current regulatory guidance documents highlight methodologies for evaluating transporter-based drug-drug interactions, whether current pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 177 publications
1
66
0
Order By: Relevance
“…Brain uptake of digoxin was approximately 35 times larger in P-gp knockout mice as compared to wildtype control mice, which indicated that P-gp is responsible for the low distribution of digoxin to the brain in vivo [57]. Digoxin is not a substrate for Bcrp [58], but other studies have indicated that the poor BBB permeability of digoxin is not explained by P-gp alone [11,38]. Verapamil has been used as a P-gp inhibitor in concentrations from 5 to 150 μM [23,[59][60][61], but it has also been shown to inhibit Mrp activity in concentrations of 5-10 μM [45,62] as well as Bcrp activity, although not in the concentration range applied here [63,64].…”
Section: Efflux Transporter Activity In Bovine Blood-brain Barrier Momentioning
confidence: 98%
See 2 more Smart Citations
“…Brain uptake of digoxin was approximately 35 times larger in P-gp knockout mice as compared to wildtype control mice, which indicated that P-gp is responsible for the low distribution of digoxin to the brain in vivo [57]. Digoxin is not a substrate for Bcrp [58], but other studies have indicated that the poor BBB permeability of digoxin is not explained by P-gp alone [11,38]. Verapamil has been used as a P-gp inhibitor in concentrations from 5 to 150 μM [23,[59][60][61], but it has also been shown to inhibit Mrp activity in concentrations of 5-10 μM [45,62] as well as Bcrp activity, although not in the concentration range applied here [63,64].…”
Section: Efflux Transporter Activity In Bovine Blood-brain Barrier Momentioning
confidence: 98%
“…However, the variations in mannitol permeabilities were apparently reduced with increasing TEER levels resulting in very low variations when the TEER was above 2,000 Ω·cm H-etoposide (P-gp and Mrp substrate) were measured on day 6 of culture ( Fig. 4) [36][37][38][39].…”
Section: The Co-culture Model Displayed High Paracellular Tightness mentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma concentrations of CsA revealed an absorbance profile of CsA with a rank order (stomach > jejunum/ileum > colon) that was consistent with changes in P-gp expression level (stomach < jejunum/ileum < colon) [92]. Differential expression of P-gp due to polymorphisms in ABCB1 could be a further source of variation across individuals; however, the specific role of individual ABCB1 polymorphisms in drug PK continues to be an area of active research [90].…”
Section: Intestinal Transportersmentioning
confidence: 84%
“…Thus, recognition by P-gp has been considered a key determinant of oral bioavailability for an array of structurally diverse drugs. Substrates for P-gp transport generally tend to be hydrophobic and are represented by high molecular weight drugs such as paclitaxol and cyclosporine A (CsA) as well as smaller sized drugs such as talinolol [90]. Although in vitro and in silico models are frequently used to identify potential P-gp substrates, the impact of P-gp on oral drug bioavailability has been predicted with varying levels of success.…”
Section: Intestinal Transportersmentioning
confidence: 99%